From Food Producer to Landscape Preserver: A Swiss Perspective on the Future of the Balinese Subak - Rachel P. Lorenzen (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
AbstractThe future of Bali’s agriculture is at a cross-roads. Tourismand urbanisation are slowly but steadily dismemberingone of the cornerstones of Balinese culture, the subak andits distinct ways of sharing water, cultivating rice andbeautifying the landscape. A combined effort is requiredof farmers, the government and society to rethink andreappraise the value of agriculture for the Balinese peopleand the economy. Such a change of perception needs toconsider the question of adequate compensation for thework farmers do in the fields, grooming 1000 year oldrice terraces, and planting, irrigating, and celebrating rice.To place Bali in a global context, I examine Switzerland’sprotective agricultural policies, rural developmentplanning and community-led initiatives which may offersome unconventional but pragmatic solutions to turn thetables for Bali’s rice sector protecting the subak institution.At last, I envisage a future for the subak and its members, anactive and proud farming community, not only famous riceproducers and fair water sharers but also recognised andappraised for their services to society as cultural landscapepreservers.